Raoultella planticola pneumonia in a patient with critical COVID-19 - Martínez Montalvo, Carlos Mauricio (2022)
Raoultella planticola is a bacterium that has been recently described in the literature as an emerging pathogen that causes urinary, abdominal, and lung infections. We present the case of a 63-year-old overweight and with dyslipidemia that was hospitalized because of a SARS-CoV-2 infection. He developed R. planticola and E. aerogenes superinfections. He was treated with cefepime for seven days, and he recovered uneventfully.